Rational Ignorance and Negative News in the Information Market - Jill McCluskey; Johan F. M. Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2007)
While the availability of infirmation has increased rapidly, the public is still considered poorly infirmed. This paper contributes to the emerging field of media economics by studying how the demand side of the media market affects news production and consumption. We show that consumers are likely to remain imperfectly infirmed on most issues and that negative news coverage is likely to dominate positive news stories because of demand side effects.
Keywords: L82; D83; 330; Media; bias; rational ignorance; negative news coverage; Mediennutzung; Marktmechanismus; Bias; Angebot; Nachfrage; Fernsehprogramm; Medienökonomik